TOURIST PERCEPTION ABOUT SAPTA PESONA IN OBJECT TOURISM DIKE OF PULAU PUNJUNG IN DHAMASRAYA REGENCY - Repijuwita, Repijuwita; Bakaruddin, Bakaruddin; Zuriyani, Elvi (STKIP PGRI Sumbar, 2013)
This study aims to know in a manner empirical description of Tourist Perception about Sapta Pesona (safety, orderliness, cleanness, coldness, beautification, friendly, and memory) in Object Tourism Dike of Pulau Punjung in Dhamasraya Regency.This study was descriptive research, the population of the research is all of visitor that come to object tourism dike of pulau punjung. Sample responden depend of insidental with total visitor 80 people, analysis that researcher uses is decriptive analysis.Tourist perception about safety is good enough classified (68.4%). Tourist perception about orderliness is good enough classified (75.2%). Tourist perception about cleanness is good classified (79.6%). Tourist perception about coldness is good classified (83.6%). Tourist perception about beautification is good enough classified (72.95%). Tourist perception about friendly is good enough classified (72.3%). Tourist perception about memory is not good enough classified (60%). In conclusion, perspetion of visitor about sapta Pesona in object tourism dike of Pulau Punjung in Dhamasraya Regency have good enough classified, because from sevent variables Sapta Pesona, 4 perseption of variables have good enough classified and the others good and not good enough.